2018
DOI: 10.1002/lary.27704
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tracheal stenosis with pirfenidone after tracheotomy: An experimental study

Abstract: Objectives In this study, pirfenidone's role about reducing tracheal stenosis by suppressing fibrosis and inflammation was examined. Methods Tracheotomy was performed on 14 rats, and their cannulas were fixed to tracheotomy area by stoma suture. Two working groups were established. Rats in the first group were given 15 mg/kg/day (1 mL pirfenidone solution) pirfenidone intraperitoneally for 10 days. In the second group as a control group, 1 mL saline solution was applied intraperitoneally. Ten days later, rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In an experimental model of tracheal wound healing Pirfenidone decreases inflammation, collagen deposition and TGF-Β1 expression [ 87 ]. In a rat model, intraperitoneal application of pirfenidone for 10 days reduced fibrosis and narrowing of the intratracheal lumen diameter, compared to the control group in which 1 mL of saline solution was injected [ 88 ]. Nintedanib is a triple tyrosine kinase inhibitor and growth factor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental model of tracheal wound healing Pirfenidone decreases inflammation, collagen deposition and TGF-Β1 expression [ 87 ]. In a rat model, intraperitoneal application of pirfenidone for 10 days reduced fibrosis and narrowing of the intratracheal lumen diameter, compared to the control group in which 1 mL of saline solution was injected [ 88 ]. Nintedanib is a triple tyrosine kinase inhibitor and growth factor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many molecules from steroids to TNF-α inhibits have been administered either systemically or locally. 26 27 However, surgical treatment is in the forefront if the cartilage scaffold is damaged. Wright et al 2 suggested meticulous assessment, effective management of comorbid cases, meticulous technique, minimizing tension, and blood flow protection for the best results.…”
Section: Discussionmentioning
confidence: 99%
“…24 Various trials have been made for the treatment of tracheal stenosis by using agents that suppress proliferation and inflammation. 21,[25][26][27] However, surgical studies have focused mostly on anastomosis tension and do not present data on the timing of tracheal surgery. 2,3,16 This study is the first study on the timing of surgery, shows the importance of the inflammatory process in the timing of the surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Tracheal injury during and after intubation or surgery causes inflammation, edema, ischemia, and eventually leads to fibrosis, resulting in severe tracheal stenosis in up to 21% of patients. 3 , 4 Recently, the number of patients who have undergone tracheostomy or intubation has increased because of the spread of coronavirus disease (COVID-19), and a large number of studies have been conducted on tracheal stenosis for efficient management after the procedure. 5 , 6 , 7 , 8 , 9 Several surgical options (e.g., balloon dilation, bronchoscopy, and tracheal resection) are currently in use to improve airway patency depending on the degree of stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Restenosis is accompanied by excessive granulation or fibrosis, and attenuated stenosis can be life-threatening. 3 , 4 Furthermore, the treatment of established fibrosis remains an unmet clinical challenge. 11 , 12 Hence, preventive approaches are urgently needed to treat tracheal stenosis, which is pivotal not only for the recovery of patients but also for reducing complications and side effects after tracheostomy or tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%